Efektivitas Penggunaan Media Digital Interaktif terhadap Minat dan Hasil Belajar Siswa di SD Negeri 81 Kota Bengkulu - Rozi Yahya; Debi Rahmat Ilahi; Maryam; Masrifah Hidayani; Ade Bayu Saputra (JURNAL ARMADA PENDIDIKAN, 2026)
This study aims to analyze the effectiveness of the use of interactive digital media on student interest and learning outcomes at SD Negeri 81 Bengkulu City. This study uses a quantitative approach with a quasi-experimental type through a nonequivalent control group design. The research subjects consisted of fifth-grade students divided into an experimental class and a control class. Data collection techniques were carried out through questionnaires to measure learning interest, tests to measure learning outcomes, and documentation as supporting data. Data analysis used normality tests, homogeneity tests, and t-tests (independent sample t-tests). The results showed that the average learning interest of students in the experimental class was higher than the control class, namely 82.5 in the high category, while the control class was 70.3 in the medium category. In addition, student learning outcomes in the experimental class experienced a significant increase with a difference of 20.4, higher than the control class of 9.3. The results of the hypothesis test showed a significance value <0.05, which means there was a significant difference between the two groups. Thus, the use of interactive digital media has proven effective in improving student interest and learning outcomes. This research provides implications that technology integration in learning can be an innovative strategy to improve the quality of education in elementary schools.